If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 = -3(x + 4) Reorder the terms: 15 = -3(4 + x) 15 = (4 * -3 + x * -3) 15 = (-12 + -3x) Solving 15 = -12 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 15 + 3x = -12 + -3x + 3x Combine like terms: -3x + 3x = 0 15 + 3x = -12 + 0 15 + 3x = -12 Add '-15' to each side of the equation. 15 + -15 + 3x = -12 + -15 Combine like terms: 15 + -15 = 0 0 + 3x = -12 + -15 3x = -12 + -15 Combine like terms: -12 + -15 = -27 3x = -27 Divide each side by '3'. x = -9 Simplifying x = -9
| -16h=12 | | 12xsquare-2x-30= | | (18z+3)+(5z-3)=180 | | 20/5.6 | | x=-10x+6x | | 6x+3-5=180 | | y=440+0.5y | | (17+4+20)+(4+20)+20= | | 7x8/10= | | -2+7x-8=21 | | 5(x+7)-4(-4x-5)=20(x+1)+8 | | -2(4x+1)=3(x+3) | | 3x+8x-8-14=0 | | 11.5x-.05x^2=650 | | ln(5x-19)=ln(2x+11) | | g+3=33 | | 4v+4v-5v= | | 4/3*pi*0.2^3 | | 75+(3x)+(4y+10)=180 | | 0=(-2x^2)+8x-16 | | (k-15)/7=(-1) | | -3x-14=-28 | | 5.6x-14.9=18.7 | | 2x+y=1.50 | | 2+3t=8-3t | | 18-x^2=39 | | 35x1/7 | | https://schoology.lsr7.org/system/files/attachments/page_embeds/m/2016-06/c7485f9626a9164a6161abff9751fc85___574f222c4eef6.png | | x+10+5=180 | | 12*k-13=59 | | 3x-8x-8-14=0 | | -104=y-67 |